Response time and length of stay in obstetric emergency management: A study in public hospital of Central Kalimantan - Dewi, Bella Rossana; Sriatmi, Ayun; Widjanarko, Bagoes (Universitas Gadjah Mada, 2025)
Purpose: This study aims to examine the relationship between response time and the length of stay (LOS) in obstetric emergency management at the public hospital of Central Kalimantan. Methods: A cross-sectional observational study was conducted using 205 medical records of pregnant women treated for obstetric emergencies between July and September 2024. Data on three types of response time—initial emergency action, obstetrician consultation, and patient disposition—were analyzed using univariate and Pearson correlation tests to assess their association with the LOS in the emergency department. Results: All patients received an initial emergency response within five minutes, indicating good early management. However, over 60% of patients experienced delays in obstetrician consultation. Most patients received timely disposition decisions, which showed the most decisive influence on patient LOS. Statistical analysis revealed a weak positive correlation between initial response time and LOS (r=0.33), a very weak negative correlation with obstetrician consultation time (r= -0.098), and a perfect positive correlation with disposition time (r=1.000). These results suggest that the speed of disposition decisions plays a critical role in determining how long patients remain in the emergency room. Conclusion: Disposition efficiency plays the most pivotal role in determining LOS. Improving administrative processes, increasing human resources, and optimizing infrastructure are essential. These findings provide practical insights for strengthening emergency service protocols and can guide health policy interventions to enhance maternal care quality in referral hospitals across Indonesia.